Orthotic insoles do not prevent physical stress-induced low back pain - Mattila, Ville M. (Springer-Verlag, 2010)
Orthotic insoles are suggested to prevent low back pain. This randomized controlled study assessed if customised orthotic insoles prevent low back pain. Healthy military conscripts (n = 228; mean age 19 years, range 18–29) were randomly assigned to use either customised orthotic insoles (treatment group, n = 73) or nothing (control group, n = 147). The main outcome measure was low back pain requiring a physician visit and resulting in minimum 1 day suspension from military duty. Twenty-four (33%) treated subjects and 42 (27%) control subjects were suspended from duty due to low back pain (p = 0.37; risk difference 4.3%; 95% CI: −8.7 to 17.3%). Mean suspension duration was 2 days (range 1–7) in both groups. Four (5%) treated subjects and eight (5%) control subjects were released from duty due to persistent low back pain (p = 0.92; risk difference 0%; 95% CI: −6 to 6%). Use of orthotic insoles is therefore not recommended to prevent physical stress-related low back pain.